Separation and recovery of graphite from spent lithium–ion batteries for synthesizing micro-expanded sorbents. (14th October 2022) - Geng, Zhiwei; Liu, Junjie; Geng, Yanni; Peng, Mingming; Xiong, Mopeng; Shi, Hui; Luo, Xubiao
Abstract : A new class of carbon adsorbent based on spent graphite is developed for the treatment of dye wastewater. Abstract : The recycling of spent lithium–ion batteries (LIBs) mainly focuses on the recycling of the valuable metals of the cathode, and little attention is paid to the graphite anode despite its high consumption and unbalanced supply and demand. Herein, we report the recovery of highly damaged spent graphite into a micro-expanded graphite (MEG) adsorbent by high-temperature oxidation using perchloric acid. The as-formed MEG not only possessed an improved layered structure and expanded specific surface area and pore volume, but also exhibited efficient electrostatic effects. Additionally, the MEG adsorbent exhibited good adsorbability to remove methylene blue (MB) with the removal rate reaching up to 100% at low concentrations, which benefited from the synergistic effect of van der Waals adsorption and electrostatic adsorption. This study provides an economical and environmentally friendly method for traditional spent graphite recycling, which is crucial for addressing the graphite supply and demand imbalance.